2020
DOI: 10.3389/fneur.2020.609384
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Diffusion-Weighted MRI Lesions to Compare the Effects of Different Heparinization Schemes in Intracranial Aneurysms Treated by Endovascular Intervention

Abstract: Objective: Heparinization is applied to prevent ischemic complications in the endovascular treatment of intracranial aneurysms, but there is no unified heparinization scheme. Diffusion-weighted imaging (DWI) can be used to evaluate ischemia after endovascular therapy for intracranial aneurysms. The goal of this study is to apply DWI to evaluate the effects of different heparinization schemes on intracranial aneurysms treated with endovascular therapy.Methods: We retrospectively reviewed 141 patients with 149 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Antiplatelet preparation is accepted as standard therapy in coil embolization for an unruptured aneurysm [ 6 , 24 ]. Several studies have shown that heparin infusion during or after the procedure is safe and effective in patients with ruptured aneurysms [ 3 , 8 , 26 ]. However, there has been little research on the incidence of microembolic infarcts according to antithrombotic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Antiplatelet preparation is accepted as standard therapy in coil embolization for an unruptured aneurysm [ 6 , 24 ]. Several studies have shown that heparin infusion during or after the procedure is safe and effective in patients with ruptured aneurysms [ 3 , 8 , 26 ]. However, there has been little research on the incidence of microembolic infarcts according to antithrombotic agents.…”
Section: Introductionmentioning
confidence: 99%